Send in the Clowns: Performing a Political Campaign in Post-Collapse Iceland - Sigurjónsdóttir, Sigríður Lára (Nordic Theatre Studies, 2018)
In the regional elections of 2010, a new political party, The Best Party (Besti flokkurinn), ran for office in Reykjavík under the leadership of mayor candidate, actor and comedian, Jón Gnarr. The Best Party’s campaign was very successful, even if it made no attempt to argue policy or (apparently) use any of the methods used in a traditional campaign. This article deals with the question of whether and how a political campaign can be an effective political performance or be seen as political activism, using some of the Best Party’s campaigning methods as a case study. The campaign is studied as a performance, drawing on the theories of Richard Schechner and Michel Foucault. While Jón Gnarr and the Best Party seemed to break with traditional politics, the article asks whether they really did that. What changes when a performer runs for office? Did the Best Party send in the clowns, or were they already there?